Spain and Portugal 1200-1492 - Correia, Jorge (2019)
Thirteenth to fifteenth were the centuries of the consolidation of the kingdoms of Portugal, Castille and Aragon, and the union of the last two in 1479 anticipated the importance of Spain during the early modern era. These were the centuries of Gothic that appeared for the first time in religious constructions in Alcobaça, Burgos or León. Nevertheless, the best of Iberian medieval architecture corresponded to what has been called Late Gothic, mainly developed during the fifteenth century and the first decades of the following one. Manueline style in Portugal, Mediterranean Gothic in Valencia and Catalonia, or Late Gothic architecture in Castille, updated the medieval tradition with new and complicated vaults and an unprecedented development of decoration.